Combating the Pandemic COVID-19: Clinical Trials, Therapies and Perspectives - Kotta, Sabna; Aldawsari, Hibah Mubarak; Badr-Eldin, Shaimaa M.; Alhakamy, Nabil Abdulhafiz; Md, Shadab; Nair, Anroop B.; Deb, Pran Kishore (Frontiers in Molecular Biosciences, 2020)
The coronavirus disease-19 (COVID-19) is caused due to the infection by a unique single stranded enveloped RNA virus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The COVID-19 has claimed many lives around the globe, and a promising solution to end this pandemic is still awaited. Till date neither an exact antiviral drug nor a vaccine is available in the market to cure or control this pandemic. Repurposed drugs and supportive measures are the only available treatment options. This systematic review focuses on different treatment strategies based on various clinical studies. The review also discusses all the current treatment plans and probable future strategies obtained as a result of a systematic search in PubMed and ScienceDirect. All the possible options for the treatment as well as prophylaxis of COVID-19 are discussed. Apart from this, the article provides details on the clinical trials related to COVID-19, which are registered under ClinicalTrials.gov. Potential of drugs based on the previous researches on SARS-CoV, MERS-CoV, Ebola, influenza, etc. which fall under the same category of coronavirus are also emphasized. Information on cell-based and immunology-based approaches is also provided. In addition, miscellaneous therapeutic approaches and adjunctive therapies are discussed. The drug repurposing options, as evidenced from various in vitro and in silico models, are also covered including the possible future solutions to this pandemic.